Vermicomposting of Sewage Sludge: Multiple Effects of Bulking Materials and Dry Solids Content on the Growth and Reproduction of the Earthworm Eisenia foetida (A Pilot Scale Study) - ABDOLI, M.A.; AZIMI, A.A.; OMRANI, GH.A.; ALLAHDADI, I.; ROSHANI, M.R. (Asian Journal of Chemistry, 2010)
The multiple effects of residual bulking agents type (paper, saw dust, straw) in mixtures with activated sludge and dry solids content (D.S., 10, 15 and 20 %) in 10 treatments on growth and reproduction of Eisenia foetida was studied in pilot scale experiments with batches of 50 earthworms for 10 weeks period. The maximum weight achieved was attained in the mixture of sludge with saw dust, dry solid 20 % (772 ± 47 mg d-1) and the highest growth rate was attained in the mixture of sludge with paper, dry solid 15 % (13.5 ± 1.41 mg d-1).The highest reproduction rate was observed in the mixture of sludge with paper, dry solid 15 % (2.5 ± 0.12 cocoon earthworm-1 week-1) compared to the lowest in the control with activated sludge alone (0.09 ± 0.02 cocoon earthworm-1 week-1).